Signaling cascades are targets for breast cancer therapy in the light of genome – wide sequencing data - L. F. Gulyaeva; M. L. Filipenko; N. E. Kushlinskii (Успехи молекулярной онкологии)
Development of next generation sequencing technologies allows to identify a large number of genetic landscape types in various cancers including breast cancer. Frequent genetic abnormalities identified using whole genome sequencing are point mutations (missense, nonsense mutations), deletions, insertions, which usually lead to activation of protooncogenes and inactivation of tumor suppressor genes. Genome sequencing of malignant tumors allowed, on one hand, to identify driver mutations in carcinogenic genes in different organs, and on the other – to use mutated genes for targeted therapy. Study of biological functions of these genes from the point of view of their contribution to carcinogenesis allows to better understand its mechanism. In this review, signaling cascades of breast cancer with identified mutated genes – targets for therapy – are analyzed.